Device‐level photonic memories and logic applications using phase‐change materials - Cheng, Z; Ríos, C; Youngblood, N; Wright, C; Pernice, W; Bhaskaran, H (John Wiley & Sons, Ltd., 2018)
Inspired by the great success of fiber optics in ultrafast data transmission, photonic computing is being extensively studied as an alternative to replace or hybridize electronic computers, which are reaching speed and bandwidth limitations. Mimicking and implementing basic computing elements on photonic devices is a first and essential step toward all‐optical computers. Here, an optical pulse‐width modulation (PWM) switching of phase‐change materials on an integrated waveguide is developed, which allows practical implementation of photonic memories and logic devices. It is established that PWM with low peak power is very effective for recrystallization of phase‐change materials, in terms of both energy efficiency and process control. Using this understanding, multilevel photonic memories with complete random accessibility are then implemented. Finally, programmable optical logic devices are demonstrated conceptually and experimentally, with logic “OR” and “NAND” achieved on just a single integrated photonic phase‐change cell. This study provides a practical and elegant technique to optically program photonic phase‐change devices for computing applications.